Fluid mechanics : - Cengel, Yunus A. (McGraw-Hill, 2006)
"Fluid Mechanics: Fundamentals and Applications" communicates directly with tomorrow's engineers in a simple yet precise manner. The text covers the basic principles and equations of fluid mechanics in the context of numerous and diverse real-world engineering examples. This text helps students develop an intuitive understanding of fluid mechanics by emphasizing the physics, and by supplying attractive figures, numerous photographs and visual aids to reinforce the physics. Fluid mechanics is a highly visual subject,and students learn more effectively by visual stimulation. Our text features more illustrations and photographs than other books in this category. Some of the figures and photographs in the text are intended to serve as a means of emphasizing key concepts that would otherwise go unnoticed; some serve as page summaries.A well-structured approach is used in problem solving while maintaining an informal conversational style. The problem is first stated and the objectives are identified, and the assumptions made are stated together with their justifications. The properties needed to solve the problem are listed separately. Numerical values are used together with their units to emphasize that numbers without units are meaningless, and unit manipulations are a important as manipulating the numerical values with a calculator. The significance of the findings is discussed following the solutions. This approach is also used consistently in the solutions presented in the Instructor's Solutions Manual.